Gluteus maximus metastasis from sacrococcygeal chordoma: A case report - Wanchen Liu, MD (Elsevier, 2022)
We reported the metastatic chordoma in the right gluteus maximus of a 73-year-old man. The patient was initially diagnosed with sacrococcygeal chordoma and treated with surgical resection. Unfortunately, he had a gluteal metastasis and recurrence and suffered the third-operation therapy. Chordoma is a rare malignant tumor and may metastasize, but the metastasis and recurrence of chordoma at the right gluteus maximus following sacrococcygeal region are extraordinarily rare. This unusual case report may be helpful to clinical workers in diagnosing chordoma.